Identification of a sex pheromone of the chrysanthemum lace bug Corythucha marmorata (Hemiptera: Tingidae) - Kisaki Watanabe (Nature Portfolio, 2017)
Abstract Although the nymphs of Corythucha marmorata form clusters on the undersides of host plant leaves, as frequently observed for Hemiptera, the adults are scattered in the vicinity of the nymph population. By investigating the biological activities of volatile secretions from the adult, we found that the secretions activated male mounting behaviour. A chemical analysis revealed that borneol was a common component of the secretions from both sexes. The absolute configuration of the natural product was the (+)-enantiomer of borneol and the optical isomer was undetectable. Although (+)-borneol showed significant sex pheromone activity against males, the antipode (−)-borneol also induced sex pheromone activity, albeit only slightly. Males may not have a strict identification mechanism based on stereochemistry. To verify the origin of this sex pheromone, we analysed the components of the essential oil of the leaves of Solidago canadensis L. (Compositae: Asteraceae), a host plant; bornyl acetate was detected to be a major component. The plant-produced bornyl acetate had different stereochemistry from the sex pheromone. The results suggested that the adults do not utilise the secondary metabolites of plants but biosynthesise this sex pheromone themselves. This is the first report on sex pheromone identification in Tingidae.